Educational approaches to improving knowledge and attitude towards dental hygiene among elementary school children - Nenny Wuri Prabawati; Lisdrianto Hanindriyo; Sri Widiati (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
The selection of appropriate dental health education methods will be beneficial in promoting dental health. This study aimed to determine the difference in the effect of role-playing method and storytelling method on knowledge and attitudes towards oral hygiene among elementary school students. The research subjects were 112 students in grade 5. The subjects were divided into 2 different treatment groups, namely 56 students in grade 5 at SD Negeri Tegalrejo I with the storytelling method and 56 students in grade 5 at SD Negeri Tegalrejo II using the role-playing method. The measuring instrument in this research was a questionnaire. The data analysis used the Mann-Whitney test and Wilcoxon Signed Ranks test because the data were not normally distributed. The results of the analysis showed that there was a significant increase over time in knowledge and attitudes carried out in 3 assessments. The mean rank for delta values between the pre-test and posttest 2 for the knowledge variable using the role-playing method was 51.29 while that using the storytelling method was 61.71. Meanwhile, the mean rank for delta values for the attitude variable using the role-playing method was 49.93, while that using the storytelling method was 63.07. The results of the delta analysis from pre-test to post-test 1 and pre-test to post-test 2 showed that the storytelling group experiences a higher increase in knowledge and attitudes than the role-playing group (p<0.05). Provision of education using a storytelling method shows better improvement in students’ knowledge and attitudes towards oral hygiene than using a role-playing method.